Aristotle’s Metaphysics: A guide for reading - Ramírez Muñoz, Fabio (Estudios de Filosofía, 2001)
The text of this article seeks, in the first part, to give bill of some historical events that have accompanied decanting of Aristotle’s work, pointing out the interpretations, difficulties and suppositions generated by the name: Metaphysics. Later on, some fundamental points are pointed out on the historical interpretation of the Aristotelian work, as well as those registered of such interpretive turns. Lastly, the author suggests an even guide for the reader, determining what would be the unitary body of the work, the annexes and the complements whose attentive reading should give the philosophical force ofthe thinker of Estagyre.